Biological variation of high sensitive Troponin T in stable heart failure patients with ischemic or dilated cardiomyopathy - Frankenstein, Lutz; Remppis, Bjoern-Andrew; Giannitsis, Evangelos; Frankenstein, Joerdis; Hess, Georg; Zdunek, Dietmar; Dösch, Andreas; Zugck, Christian; Katus, Hugo (Clinical research in cardiology, 2011)
High sensitive Troponin (hsTn) assays enable detection of minimal marker elevation in heart failure patients previously deemed Troponin negative. Biovariability, reference change values (RCV), and index of individuality (II) have not been previously described for hsTnT although serial testing is important in interpreting low concentrations. For these values, a difference between ischemic heart disease (IHD) and dilated cardiomyopathy (dCMP) appears conceivable.